Model Pembelajaran Full Day School Dalam Inovasi Program Tahfidzul Qur’an Di MI Ar-Roihan Lawang - Ana Maslihatul Izzah; Ahmad Ma’ruf; Muhammada (Al-Abshor : Jurnal Pendidikan Agama Islam, 2024)
Full day scholl according to etymology is the word full day school derived from the English language. Full means full, day means day, while school means school. And if combined, it means a full day of school. Meanwhile, according to terminology, there are several opinions that explain the meaning of full day school. The method used in this study is qualitative research, namely research that produces descriptive data. Qualitative research methods are research methods based on the philosophy of post-positivism, used to research on the natural condition of objects. Based on the results of the interviews obtained in the following data exposure, a presentation of the data of the research results will be presented that focuses on the Full Day School learning model in the innovation of the Tahfidzul Qur''an program. The Full Day School learning model at MIT Ar Rohan Lawang Malang has a positive effectiveness and contribution in the innovation of the Tahfidzul Qur''an program. With longer learning times, a supportive educational environment, and integration with the academic curriculum, students can optimize their memorization of the Qur'an as well as develop a deeper understanding of Islamic teachings. In this case, the Full Day School at MIT Ar Rohan Lawang Malang plays an important role in facilitating progress and innovation in the Tahfidzul Qur''an program. The purpose of this study is to find out and describe the full day school learning model as an innovation of tahfidzul qur'an at Madrasah Ibtidaiyah Terpadu Ar roihan Lawang Malang. And the purpose of this study is to analyze the effectiveness or influence of the full day school learning model in the tahfidzul Qur'an innovation at MIT Ar Roihan Lawang, Malang. Abstrak Full day scholl menurut etimologi adalah kata full day school berasal dari bahasa inggris. Full artinya penuh, day artinya hari, sedangkan school yang mempunyai arti sekolah. Dan jika digabung mengandung arti sekolah sehari penuh. Sedangkan menurut terminologi, ada beberapa pendapat yang menjelaskan tentang pengertian full day school.Metode yang digunakan dalam penelitian ini adalah penelitian kualitatif, yaitu penelitian yang menghasilkan data deskriptif. Metode penelitian kualitatif adalah metode penelitian yang berlandaskan pada filsafat post-positivisme, digunakan untuk meneliti pada kondisi objek yang alamiah.Berdasarkan hasil wawancara yang diperoleh dalam paparan data berikut ini akan disajikan paparan data hasil penelitian yang berfokus pada model pembelajaran Full Day School dalam inovasi program Tahfidzul Qur''an. , model pembelajaran Full Day School di MIT Ar Rohan Lawang Malang memiliki efektivitas dan kontribusi yang positif dalam inovasi program Tahfidzul Qur''an. Dengan waktu belajar yang lebih lama, lingkungan pendidikan yang mendukung, dan integrasi dengan kurikulum akademik, siswa dapat mengoptimalkan hafalan Al-Qur''an mereka serta mengembangkan pemahaman yang lebih mendalam tentang ajaran Islam. Dalam hal ini, Full Day School di MIT Ar Rohan Lawang Malang berperan penting dalam memfasilitasi kemajuan dan inovasi dalam program Tahfidzul Qur''an. Tujuan dilakukannya penelitian ini untuk mengetahui dan mendeskripsikan model pembelajaran full day school sebagai inovasi tahfidzul qur’an di Madrasah Ibtidaiyah Terpadu Ar roihan Lawang Malang. Serta tujuan penelitian ini ialah menganalisis efektivitas atau pengaruh model pembelajaran full day school dalam inovasi tahfidzul Qur''an di MIT Ar Roihan Lawang, Malang